Cooperación y competencia como antecedentes de la innovación de producto: Aplican las empresas nuevas y establecidas una lógica diferenciada? - Raquel Antolín-López; Javier Martínez-del-Río; José Céspedes-Lorente (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– The relationships between different types of cooperation and rivalry and product innovation are examined in this article, differentiating between new and established companies. The hypotheses proposed suggest different patterns of cooperation. For new companies, the most effective types of cooperation are those which can lower costs and reduce risks (small and medium size companies, other new companies, financial bodies and knowledge centres). On the other hand, established companies may benefit more by cooperating with other established companies. Furthermore, the relationship between intense rivalry and product innovation is stronger for established companies than for new ones. The results obtained, using a sample of 3,528 companies in geographical clusters of 32 European countries, confirm the established hypotheses in general terms. These results have interesting implications for research into entrepreneurship, cooperation and competitive dynamics.
Keywords: L26; M13; O31; O32; 330; New companies; Cooperation; Rivalry; Innovation; Cluster